Investigating the information behavior of chess student-athletes at UP Diliman with implications for self-training: needs, sources, motivations, and challenges - Bunao, Katherine T.
The importance of information cannot be overstated, as it is consistently gathered, scrutinized, and applied across various contexts. For student-athletes, the ability to seek, process, and apply relevant information is crucial for both their academic and athletic success. However, there is minimal literature that specifically explores their athletic training aspects, making this study vital.